Respon Klon Karet terhadap Frekuensi Penyiraman di Media Tailing Pasir Pasca Penambangan Timah - Ismed Inonu (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2011)
Sand tailings derived from tin post-minings activities have high porosity, low water holding capacity, and low organic matter content. These conditions causes soil water defi cit, especially in dry season. To increase the successful of sand tailings revegetation with rubber tree, it is important to select some rubber tree clones based on their adaptability on the sand tailings conditions, especially drought stress. This research aimed to study the response of several rubber tree clones to the frequency of watering on sand tailings. The experiment was conducted in a plastic house at the experimental station of Agrotechnology Study Program of Bangka Belitung University, Sungailiat for 4 months. The experimental design was a factorial randomized block design with two factors and three replications. The fi rst factor was the frequency of watering (every day, every 3 days, and every 5 days), the second factor was a combination of recommended rootstock clones and recommended latex clones (clone GT 1 + PB 260, GT 1 + IRR 118, and PB 260 + BPM 24). The results showed that watering every 5 days caused drought stress resulted in impaired growth of rubber in sand tailings media derived from tin post-mining. The combination of rootstocks and scions PB 260 + BPM 24 and PB 260 + IRR118 were categorized as moderately tolerant clones while GT 1 + PB 260 was categorized as sensitive clones to drought stress in the sand tailings media.Keywords: drought tolerance, watering frequency, rubber tree clones, sand tailings